The Influence of the SPEOS Method (Stimulation oF Endorphine Massage, Oxytocine and Sugestion) on Breast Milk Production in Breastfeeding Mother 0 – 6 Months - Julianti, Neneng (Universitas Islam Lamongan, 2023)
According to the Ministry of Health 2020 Nationally, the coverage of exclusive breastfeeding in infants 0-6 months in Indonesia is 66.1%, the rate of exclusive breastfeeding in Indonesia is higher than the global rate, thus the achievement of exclusive breastfeeding has not yet reached the target. Based on the results of a preliminary study conducted by researchers at Hamlet 1, Bantarjaya Village, Pebayuran District, Bekasi Regency, there were 64% of breastfeeding mothers who still failed to provide exclusive breastfeeding with several kinds of causative factors and had no or never had health workers apply the SPEOS method (Endorphin Massage Stimulation, Oxytocin and Suggestion) when providing midwifery care to motherspost partum. The purpose of this study was to determine the effect of the SPEOS method (Endorphin, Oxytocin & Suggestive Massage Stimulation) on Breast Milk Production in Breastfeeding Mothers 0-6 months in Bantarjaya Village, Bekasi Regency in 2022.The research method was carried out using a quantitative research method with an approachQuasi Experimentsby using a statistical testWilcoxon (Not Normal Distribution). The population in this study were all breastfeeding mothers 0-6 months in Bantarjaya Village, namely 40 people. The sample in this study were breastfeeding mothers 0-6 months in Bantarjaya Village using the total sampling technique, the number of samples was 40 people. Data collection with a questionnaire. Data analysis is univariate, bivariate and multivariate analysis. The output of this research is an article published in an Accredited National Journal and an IPR in the form of a pocket book of endorphin massage and oxytocin massage. The results of the study showed that of the 40 breastfeeding mothers, based on their milk production during the pretest, the most were breastfeeding mothers whose milk production was less, namely 57.5% compared to breastfeeding mothers who produced a lot of milk. After doing the SPEOS method (endorphin, oxytocin & suggestive massage stimulation)(post test), breastfeeding mothers whose milk production experienced an increase to 30 people (75%). Meanwhile, breastfeeding mothers whose milk production was less reduced to 10 people (25%).Statistical test results are knownasymp. Sig has a value of 0.000 (P <0.05), so it can be concluded that the hypothesis is accepted. This means that there is a difference between the resultsPretest andPosttest, so it can also be concluded that there is an effect of the SPEOS method (Stimulation of endorphin, oxytocin & suggestive massage) with an increase in milk production in breastfeeding mothers 0-6 months in Bantarjaya Village, Pebayuran District, Bekasi Regency in 2022. The dominant characteristic variable is Parity. The role of health workers and the health service is needed to increase the knowledge and motivation of mothers in carrying out the SPEOS method (Stimulation of endorphin, oxytocin & suggestive massage) the aim is to increase milk production to prepare for the achievement of exclusive breastfeeding for the growth and development of babies through community empowerment such as cadres, community leaders as well as religious figures.